Effect of thyroid dysfunction on hemoglobin A1c in polycystic ovary patients during ovulation induction trials. - Mahdi, Hiba S.; Sudek, Hanan L.; Salman, Abdulaali H. (Journal of the Faculty of Medicine Baghdad, 2014)
Background: Polycystic ovary syndrome (PCOS) is one of the most common female endocrine disorders leading to infertility. Majority of women with PCOS have insulin resistance and elevated hemoglobin A1c.The presence of thyroid dysfunction may affect the levels of HbA1c and the results of ovulation induction programs.                                                                                                           Objectives: To evaluate the level of serum hemoglobin A1c according to the type of thyroid dysfunction in polycystic ovary patients during ovarian stimulation trials.                  Patients and Methods: Eighty three polycystic ovary patients were enrolled in this study, attending the infertility clinic in Al-Yarmouk Teaching Hospital, in the period between November 2012 and May 2013. After thorough history and examination blood samples were withdrawn for the estimation of LH, FSH, testosterone, prolactin, TSH, T3, T4 and A1C in day 2 or 3 of the menstrual cycle, Progesterone was determined in day 21 of the cycle. Ultrasound was done also at cycle day 3 for antral follicles measurements. After diagnosing PCOS the patients were divided into 3 groups, euthyroid group (control), hypothyroid and hyperthyroid groups. Ovulation induction treatment was given and ultrasound was done at the day of hCG injection.                                          Results: There was no significant difference between control and patients groups regarding age (26.31 ± 5.04 Vs 27.17 ± 5.76) and BMI (31.7 ± 5.69Vs 29.25 ± 6.28).HbA1c level was significantly different between the control and patients group with a significant positive correlation between HbA1c and TSH. In clomiphene citrate treated groups, Hb A1c level, the number of antral follicles and the size of follicles at day of hCG injection were not significantly different between the patients and control groups.                                                                                                                                Conclusions: HbA1c level is significantly affected by thyroid dysfunction in PCOS patients as it is higher in the Hypothyroid group and lower in the Hyperthyroid group. Using Clomiphene citrate in PCOS does not significantly increase the mean size of follicles after ovarian stimulation in patients with thyroid dysfunction from that in Euthyroid ones.